Recovery and subsequent characterization of polyhydroxybutyrate from Rhodococcus equi cells grown on crude palm kernel oil - Altaee, Nadia; Fahdil, Ayad; Yousif, Emad; Sudesh, Kumar (Taibah University, Madinah, Kingdom of Saudi Arabia, 2016)
The gram-positive bacterium Rhodococcus equi was isolated from fertile soil, and mineral salt media (MM) and trace elementswere used to provide the necessary elements for its growth and PHB production in addition to using crude palm kernel oil (CPKO) 1%as the carbon source. Gas chromatography (GC) demonstrated that the composition of the recovered biopolymer was homopolymerpolyhydroxybutyrate (PHB). The strain of the present study has a dry biomass of 1.43 (g/l) with 38% PHB, as determined by GC.The recovered PHB was characterized by NMR to study the chemical structure. In addition, DSC and TGA were used to study thethermal properties of the recovered polymer, where the melting temperature (Tm) was 173◦C, the glass transition temperature (Tg)was 2.79◦C, and the decomposition temperature (Td) was 276◦C. Gel permeation chromatography (GPC) was used to study themolecular mass of the recovered PHB in addition to comparing the results with other studies using different bacteria and substrates,where the molecular weight was 642 kDa, to enable its usage in many applications. The present study demonstrated the use of aninexpensive substrate for PHB production, i.e., using gram-positive bacteria to produce PHB polymer with characterization.